Relación entre la osificación de sutura media palatina con la maduración vertebral cervical y la edad dental (2024)
Among the malocclusions that affect the craniofacial complex, there is an alteration in the size of the jaw. When compression of the jaw is found, it is important to identify the appropriate time to perform expansion procedures and achieve success in the treatment. To decide the type of expansion, it is crucial to know the state of ossification of the midpalatal suture, which can be identified in cone beam computed tomography (CBCT) images (Angelieri and Cevidanes, 2013). These images are not part of the routine examinations sent to patients, they are 10 times more expensive than commonly sent x-rays and involve greater radiation. (Jaju and Jaju, 2015)